Economics and Economic Order of Societies* - Zbigniew Hockuba (Studia i Materiały)
Departing from the distinction proposed by J. Buchanan between thinking in economics in terms of the theory of choice and analysis in categories of exchange and coordination, we claim that the Hayekian concept of economic order has a significant heuristic potential and can be fruitfully used to explain some important socio-economic phenomena. The goal of this paper is to confirm this claim through the application of the concept of economic order in the analysis of economic transformation and the discussion of the relation between economic order and moral norms. The paper is organised as follows. Section I contains introductory remarks. In section II, the two systems of economic thinking and reasoning: the theory of choice and analysis in categories of exchange and coordination are briefly presented. Section III contains a discussion of the concept of economic order, its origin, relation to the Freiburg School notion Ordo, and J. Buchanan’s perspective on the market and exchange. In section IV, two areas of the application of the concept of economic order are presented: a) systemic transformation as a change in formal and informal institutions, their subjective representation by economic agents and the complex economic order, b) a relation between economic order and moral norms. Conclusions are drawn in section V.